Chapter Prefazione - Cruciani, Sante (Studi e saggi, 2023)
Bruno Trentin's biography represents an ideal prism on the Lefts from the Cold War to globalization, technological innovation and integration processes, and the dialectic between equality and freedom in international communism, the labor movement and European socialism. In addition to his role as "passeur" between Italy and France, Trentin also established a transnational circuit of intellectuals, trade union and political leaders, communists, socialists, democratic Catholics, who crossed the orthodoxies of the Twentieth century, in the name of trade union autonomy and a libertarian socialism based on the indissoluble relationship between Rights, Europe, Federalism. With such interpretative keys, the essay explores the period of the CGIL General Secretary, the election to the European Parliament and the last political interventions (1988-2007).